Společensko-ekonomické aspekty prevence závislosti - Skokanová, Andrea (Univerzita Pardubice, 2006)
Tato bakalářská práce je zaměřená na problematiku drog a příčiny s tím souvisejícími. Zabývá se drogami, drogovou závislostí, prevencí, koncepcí protidrogové politiky v České republice, společensko-ekonomickými dopady na společnost, zdravotními a sociálními důsledky. Zahrnuje také vyhodnocení dat z výzkumu primární prevence na dvou základních školách.

The bachelor work specializes in the problems of drugs and causes related with it. It also deals with drugs, drug´s dependence, prevention, the conception of counter-drugs policy in the Czech Republic, social-economic impacts on the society, health and social consequences. It comprise also data evaluation from the primary prevention research at two elementary schools.
Social-economic aspects dependence prevention
Keywords: Drugs; drug´s dependence; prevention; aspects; counter-drugs policy; Financing; Drogy; drogová závislost; prevence; aspekty; protidrogová politika; financování